Elicitation Study Based on the Theory of Planned Behaviour that analyses the intention to Adopt Electronic Commerce in the Elderly - Nadia Soto-Hernández; Elizabeth E. Grandón; Patricio Ramírez-Correa (Multidisciplinary Business Review)
The adoption of electronic commerce has been widely studied through various theories. However, the elderly segment has been relatively excluded from these studies. Focusing on older people is relevant due to the significant increase in the aging of the world population and the digital divide that marginalises them from the benefits of technological advances. In this context, and based on the theory of planned behaviour, this study aims to build an instrument that measures older people’s behavioural, normative, and control beliefs about electronic commerce. The instrument is developed through an elicitation study following a qualitative methodology. Thirty-four older Chilean people were interviewed based on a questionnaire of open questions associated with consequences, social referents, and obstacles to the use of electronic commerce. The 443 responses were examined through content analysis, which led to the determination of measures of behavioural beliefs, evaluation, normative beliefs, motivation to comply, control beliefs, and perceived facilitation. The measures determined are the basis for the proposal of a novel instrument that contains 66 items personalised to this age group. The findings of new variables obtained from the elicitation process highlight the importance of considering ad-hoc measurement scales in the development of public policies to promote the use of electronic commerce in older people. Future research could validate this instrument through a quantitative study in a sample of older people. The methodology followed can be replicated in this population to understand the use of other information technologies such as smartphones and social network sites, among others.